Knowledge, attitudes and practices regarding breast cancer prevention among women of childbearing age: a study conducted in the IPEKO health district, Mbandaka health zone, Mbandaka city, Equateur Province, DRC - BOKWALA MBANGO Marlène; NSAMBI E MBULA Jean Baptiste; Laurent BOSONGO; NYAFE BASELE HenriStanley; MANZUKA Mbambwa (International Journal of Scientific Research and Innovative Studies, 2026)
Introduction: Breast oncology is advancing in the Congo, but the lack of organised screening leads to disproportionately high mortality rates. In Mbandaka, this burden is exacerbated by the absence of technical facilities, a marked lack of knowledge and cultural barriers that lead to the use of traditional healers. Objective: This study assesses the knowledge, attitudes and practices of women in the IPEKO area regarding breast cancer to optimise early detection. Methodology: A quantitative cross-sectional survey was conducted among 384 women (aged 15–49) via face-to-face interviews using a questionnaire, with data analysed using SPSS and Excel. Results: Whilst 58.3% of respondents were aware of the disease, only 18.5% were familiar with its warning signs. Furthermore, 38% attributed the condition to mysticism, 52% refused surgery due to denial, and only 14% practised monthly self-examination. Academics (OR = 7.24) and women perceiving a high risk (OR = 6.48) perform self-examination significantly more often (p < 0.001). Discussion: The semantic disconnect confirms the superficial nature of mass campaigns. Local resistance to mastectomy dramatically delays medical treatment. Conclusion: There is an urgent need to de-medicalise the teaching of self-examination so that it can be integrated as a standard part of women’s personal hygiene. Local collaborative synergy is essential to break down taboos. Keywords: Knowledge, Attitudes, Practices, women of childbearing age, prevention, breast cancer. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/680